Helicobacter pylori in Cholecystectomy Specimens-Morphological and Immunohistochemical Assessment - Patnayak, Rashmi (J Clin Diagn Res, 2016)
INTRODUCTION: Helicobacter pylori (H.pylori) is associated with gastritis, peptic ulcer, gastric carcinoma and gastric lymphoma. Current literature describes presence of H.pylori in various extra-gastric locations and its association with many diseases. Apart from the conventional location of gastric and duodenal mucosa, H.pylori have been isolated and cultured from gallbladder. AIM: Analysis of cholecystectomy specimens to detect H.pylori by means of immunohistochemical staining. MATERIALS AND METHODS: There were a total of 118 cholecystectomy specimens received in the Department of Pathology in three months duration. We have performed immunostaining for H.pylori in 45 consecutive cases of cholecystectomy specimen. Clinical and other investigational information were retrieved from the medical records department. For each case, routine Haematoxylin and Eosin stain was studied. Immunohistochemistry (IHC) was done using purified polyclonal Helicobacter pylori antiserum. RESULTS: Majority of the patients had undergone laparoscopic cholecystectomy for the presenting complaint of right hypochondrial pain. Multiple pigmented stones were present in majority (27/45) of them. Immunostain for H.pylori was positive in ten cases. Six of these cases had pigmented gall stones, two had stones not specified and in two of the cases there were no stones. CONCLUSION: Helicobacter pylori is present in gall bladder and is commonly seen in association with stones. A more detailed study of cholecystectomy cases (both neoplastic and non-neoplastic) with serological, culture and molecular data of H.pylori is desirable to study the pathogenesis of cholecystitis, its association with gall stones and other gall bladder disorders.